2014
DOI: 10.3109/21691401.2014.955108
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between the cytotoxic effects of pure curcumin and curcumin-loaded PLGA-PEG nanoparticles on the MCF-7 human breast cancer cell line

Abstract: Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer death among women worldwide. Herbal medicines have tremendous potential as promising agents for the treatment of cancer. Curcumin is a natural polyphenol which has many anticancer effects. Because of its low aqueous solubility, low bioavailability, and quick degradation and metabolism, curcumin was released using PLGA-PEG nanoparticles. Herein, the efficiency of pure curcumin and curcumin-loaded PLGA-PEG in MCF-7 human breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…The literature shows that the cytotoxic effect of a nanoformulation of curcumin is equal to or higher than that of free curcumin. 38,39 This does not match our results where the cytotoxic effect of CuCs was lower than that of free curcumin. This might be due to i) the lower % of the entrapment efficiency, ii) the nature of the nanocarrier, which is different in the current study than in previous studies, and iii) the antioxidant properties of CsNPs as previously reported by Nair et al 40 Further extensive investigations using simulated CompuSyn software (Linear Interaction Effect) were conducted to investigate possible additivity between curcumin and CsNPs, which might predict the synergistic effect of CuCs nanocomposite as antiviral activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The literature shows that the cytotoxic effect of a nanoformulation of curcumin is equal to or higher than that of free curcumin. 38,39 This does not match our results where the cytotoxic effect of CuCs was lower than that of free curcumin. This might be due to i) the lower % of the entrapment efficiency, ii) the nature of the nanocarrier, which is different in the current study than in previous studies, and iii) the antioxidant properties of CsNPs as previously reported by Nair et al 40 Further extensive investigations using simulated CompuSyn software (Linear Interaction Effect) were conducted to investigate possible additivity between curcumin and CsNPs, which might predict the synergistic effect of CuCs nanocomposite as antiviral activity.…”
Section: Discussioncontrasting
confidence: 99%
“…One major advantage of lipid vesicles is its ability to fuse with cellular membranes or membranes of intracellular organelles. This allows for much versatility in their ability to deliver drugs to different sites of the cells (Abbasi et al 2016a, Abbasi et al 2016b, Alizadeh et al 2016, Chang 1966, Chung et al 2016, Daraee et al 2016a, Daraee et al 20146b, Davoudi et al 2014, Eatemadi et al 2016, Ebrahimi et al 2016, Fekri Aval et al 2016, Hosseininasab et al 2014, Nasrabadi et al 2016, Sadat Tabatabaei Mirakabad et al 2016.…”
Section: Drug Delivery Based On Mnpsmentioning
confidence: 99%
“…Absorbance of the formazan solution was measured at 570 nm (650 nm background) on a Spectra Max plate reader. The results were expressed as mean  standard deviation of 3 measurements (Tabatabaei Mirakabad et al 2015, Luo et al 2014). …”
Section: In Vitro Cytotoxicity Studymentioning
confidence: 99%